CaV2.1 voltage activated calcium channels and synaptic transmission in familial hemiplegic migraine pathogenesis - Uchitel, Osvaldo Daniel (2011)
Studies on the genetic forms of epilepsy, chronic pain, and migraine caused by mutations in ion channels have given crucial insights into the molecular mechanisms, pathogenesis, and therapeutic approaches to complex neurological disorders. In this review we focus on the role of mutated CaV2.1 (i.e., P/Q-type) voltage-activated Ca2+ channels, and on the ultimate consequences that mutations causing familial hemiplegic migraine type-1 (FHM1) have in neurotransmitter release. Transgenic mice harboring the human pathogenic FHM1 mutation R192Q or S218L (KI) have been used as models to study neurotransmission at several central and peripheral synapses. FHM1 KI mice are a powerful tool to explore presynaptic regulation associated with expression of CaV2.1 channels. Mutated CaV2.1 channels activate at more hyperpolarizing potentials and lead to a gain-of-function in synaptic transmission. This gain-of-function might underlie alterations in the excitatory/ inhibitory balance of synaptic transmission, favoring a persistent state of hyperexcitability in cortical neurons that would increase the susceptibility for cortical spreading depression (CSD), a mechanism believed to initiate the attacks of migraine with aura.